Celowość wdrażania koncepcji CRM we współczesnych przedsiębiorstwach na przykładzie firmy Wix - Filtron - Teneta-Skwiercz, Dorota (The Usefulness of Implementing the Idea of CRM in Modern Enterprises on the Example of Wix - Filtron Company, 2006)
The article is a part of discussion on the usefulness of implement inculcating the CRM concept in modern companies. Apart from CRM's essence and reasons for its growing popularity, and conditions of successful implementation, premises, course, and results the implementation are presented. All these have been taken out of research done in one of Polish companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 464-469